Transmission from seed to seedling and elimination of alfalfa viruses - Li, Jin; Shang, Qiaoxia; Luo, Yingning; Wei, Shuhua; Zhao, Chaoyang; Ban, Liping (Frontiers in Plant Science, 2024)
Introduction Viral diseases have become a vital factor limiting the development of the alfalfa (Medicago sativa) industry. Six viruses infecting alfalfa with a high incidence rate are Alfalfa mosaic virus (AMV), Medicago sativa alphapartitivirus 1 (MsAPV1), Medicago sativa alphapartitivirus 2 (MsAPV2), Medicago sativa deltapartitivirus 1 (MsDPV1), Medicago sativa amalgavirus 1 (MsAV1), and Cnidium vein yellowing virus 1 (CnVYV1). The purpose of this study was to develop preventive measures against these viruses by investigating their transmission through alfalfa seeds. Methods In this study, we investigated the transmission rate of alfalfa viruses from seed to seedling by PCR, determined the location of viruses in seed by dissecting seed embryos and seed coat, tracked the changes of viruses in seedlings, and finally discover effective elimination measures for alfalfa viruses from 16 measures. Results and discussion Our results demonstrated that all these six viruses could be transmitted from alfalfa seeds to seedlings with the transmission rate ranging from 44.44% to 88.89%. For AMV, MsAPV2, and MsAV1, the viral load was significantly higher in the seed coats than in the seed embryos; however, it did not show significant differences between these two parts of the seeds for MsAPV1, MsDPV1, and CnVYV1. Dynamic accumulation analysis of AMV and MsAPV2 indicated that the viral load in plants increased continuously in the early growth stage, making it important to inactivate these viruses prior to their seed-to-seedling transmission. Sixteen treatments including physical, chemical, and combinations of physical and chemical measures were compared in terms of their elimination efficiency on AMV and MsAPV2 and impacts on seed germination. The results showed that soaking alfalfa seeds in sterile distilled water for 2h + 2% NaClO for 1h or 2% NaClO for 1h were more promisingly applicable because it could significantly reduce AMV and MsAPV2 particles in both seeds and seedlings. Our data revealed a route of virus transmission in alfalfa and shed light on the discovery of a highly efficient method for the management of alfalfa viral diseases.